Resistance of Antarctic black fungi and cryptoendolithic communities to simulated space and Martian conditions - Onofri, Silvano; Barreca, Donatella; Selbmann, Laura; Daniela, Isola; Rabbow, Elke; Horneck, Gerda; de Vera, Jean Pierre; Hatton, Jeason; Zucconi Galli Fonseca, Laura (Centralbureau voor Schimmelcultures, 2008)
Dried colonies of the Antarctic rock-inhabiting meristematic fungi Cryomyces antarcticus CCFEE 515, CCFEE 534 and C. minteri CCFEE 5187, as well as fragments of rocks colonized by the Antarctic cryptoendolithic community, were exposed to a set of ground-based experiment verification tests (EVTs) at the German Aerospace Center (DLR, Köln, Germany). These were carried out to test the tolerance of these organisms in view of their possible exposure to space conditions outside of the International Space Station (ISS). Tests included single or combined simulated space and Martian conditions. Responses were analysed both by cultural and microscopic methods. Thereby, colony formation capacities were measured and the cellular viability was assessed using live/dead dyes FUN 1 and SYTOX Green. The results clearly suggest a general good resistance of all the samples investigated. C. minteri CCFEE 5187, C. antarcticus CCFEE 515 and colonized rocks were selected as suitable candidates to withstand space flight and long-term permanence in space on the ISS in the framework of the LIchens and Fungi Experiments (LIFE programme, European Space Agency).